Gambaran Budaya Organisasi Dan Konsep Diri Kepala Sekolah: Studi Deskriptif - Rina Nurhidayati; Rimsa Rusmiland (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
This study used a descriptive approach and was conducted on elementary school principals in Jagakarsa District, South Jakarta. The aim was to analyze the influence of organizational culture and self-concept on principal decision-making. The study population included all elementary school principals in Jagakarsa District, namely 62 people; the sample studied was 54 principals, selected using the Simple Random Sampling technique. Data were collected through a 5-point Likert scale questionnaire, consisting of 24 statements for the organizational culture variable and 25 statements for the self-concept variable. Data analysis was conducted descriptively to describe the condition of organizational culture and self-concept of school principals objectively. The results showed that a positive organizational culture goes hand in hand with a good self-concept of school principals, thus supporting the creation of a conducive school environment. This finding emphasizes the importance of strengthening organizational culture as a supporting factor in the formation of a positive self-concept of school principals.